The odyssey to next-generation computers: cognitive computers (κC) inspired by the brain and powered by intelligent mathematics - Wang, Yingxu; Widrow, Bernard; Hoare, C. A. R.; Pedrycz, Witold; Berwick, Robert C.; Plataniotis, Konstantinos N.; Rudas, Imre J.; Lu, Jianhua; Kacprzyk, Janusz (Frontiers in Computer Science, 2023)
Cognitive computers (κC) are intelligent processors advanced from data and information processing to autonomous knowledge learning and intelligence generation. This work presents a retrospective and prospective review of the odyssey toward κC empowered by transdisciplinary basic research and engineering advances. A wide range of fundamental theories and innovative technologies for κC is explored, and a set of underpinning intelligent mathematics (IM) is created. The architectures of κC for cognitive computing and Autonomous Intelligence Generation (AIG) are designed as a brain-inspired cognitive engine. Applications of κC in autonomous AI (AAI) are demonstrated by pilot projects. This work reveals that AIG will no longer be a privilege restricted only to humans via the odyssey to κC toward training-free and self-inferencing computers.